Evaluation of the Effect of Sodium Hypochlorite Irrigant on Pull-out Bond Strength of FRC Posts Using Different Resin Cements - Alireza Boruziniat; Noushin Arjmand; Atefeh Atoufi (Mashhad University of Medical Sciences, 2014)
Introduction: To evaluate the effects of using sodium hypochlorite irrigant on pull-out bond strength of self-etch and self-adhesive resin cements to dentin. Methods: Sixty intact premolars were decoronated and the root canals were prepared by step-back technique. The teeth were divided into two groups according to the irrigant used during root canal treatment: 5.25% sodium hypochlorite and normal saline. The canals were obturated and after 48 hours storage, 8mm depth post space was prepared with application of normal saline as irrigant. Then, each group was divided into two subgroups depending on the type of the cements used for cementation of fiber reinforced composite (FRC) posts (Panavia F2or Embrace). The pull-out bond strength test was evaluated. Statistical analysis was performed by Two-way AONVA. Results: The type of cement had no statistically significant effect on the bond strength; however, the type of irrigant was statistically effective. There was no interaction between two independent variables. The application of sodium hypochlorite significantly decreased the pull-out bond strength in Embrace cement in comparison with the use of normal saline. Conclusion: The type of irrigants used in endodontic treatment may affect on bond strength of FRC posts cemented by self-adhesive cements.